Rethinking Education in the Raw Materials Sector through Tailor-Made Teaching Methodologies - Elena Yaneva; Spyros Papaefthymiou; Lea Daling; Sibila Borojević Šoštarić; Ildiko Merta (Materials Proceedings, 2022)
This article presents a methodology applied to the design of a tailor-made program for teaching staff that addresses the needs of high-level educational institutions in the Eastern and South-Eastern European (ESEE) region. The tailor-made program was implemented as a one-week online course for 22 “Trainees” from six ESEE universities earlier in 2021. “Trainees” from six participating universities are currently developing acceleration programs, planned to occur continuously until 2024, increasing the percentage of the trained academic staff to >50% at each of the six universities. During that period, 240 students will benefit from 140 improved RawMaterials-related courses, improving their learning and understanding.